The First Case of COVID-19 in South Kalimantan - Muhammad Nor; Haryati Haryati (Faculty of Medicine Universitas Airlangga, 2020)
Background: In December 2019, a series of acute respiratory syndromes occurred in Wuhan, China. This syndrome became known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The sudden appearance and rapid global spread of SARS-CoV-2 led World Health Organization (WHO) to declare it as a pandemic disease on March 11, 2020. We will report the first case COVID-19 in South Kalimantan.Case: A 44-year-old man was presented with fever, 7 days before admission. The patient also complained about cough with white phlegm and shortness of breath, accompanied by nausea with heartburn and decreased of appetite. He confessed that he just returned from local transmission areas of COVID-19. From physical examination, it was found SaO2 92% room air with bronchial sounds and ronchi in the lung. Chest X-ray showed peripheral infiltrates and diagnostic swab with RT-PCR in the oropharynx and nasopharynx showed that the patient was infected with SARS-CoV-2. HbsAg marker on this patient was also reactive. The patient then received supportive therapy as well as antiviral therapy. After 10 days of treatment, the patient was already free from the symptom, but swab evaluation remained positive. On the 31st day of treatment, the patient was finally declared cured with a negative swab result.Conclusion: The number of COVID-19 cases has increased from time to time. Holistic treatment and rapid detection greatly affect the prognosis of this disease. Prevention through health protocols is also very important to reduce its spread.